Das Legionslager Tilurium : 15 Jahre archäologischer Ausgrabungen : 1997 - 2011 - Sanader, Mirjana (Array, 2015)
The legionary fortress at Tilurium is one of two known legionary fortresses situated in the Roman province of Dalmatia. According to Pliny (N.H. III, 142) the fortress was constructed on the location of a well-placed and strategic, former Illyrian hill fort. The site is today situated within the modern village of Gardun nearby the small town of Trilj and 30 kilometers into the hinterland of the province’s capital Salona. The importance of the fortress at Tilurium had been very well documented in the scientific literature, although archaeological excavations had never been undertaken there before the current project. The reason for such a great interest in the site is that it has yielded more than a hundred inscriptions, mostly on stelae, raised for the legionaries of the Seventh legion. Despite the great interest of experts in Tilurium and its extraordinary epigraphic sources, answers to some important questions had not been established.These primarily concerned the question of the fortress’ foundation date (and therefore depended on the deployment of Roman legionary troops during the early Principate in Illyricum). In addition, the parameters of the camp and its precise position on the hill fort were still unknown. In order to establish the ch ronology of its construction a nd its stratigra phic context, archaeological excavations at Tilurium started in 1997.General results of the past 15 seasons of excavations reveal that the fortress was built on the north-eastern part of the plateau which rise s above the right bank of the Cetina River and covers an area of 12 ha. It was built of stone with the extensive use of timber. Within the ramparts (partly discovered) are imposing remains of Roman camp architecture (military barracks, water cistern, water canal and drain), all of them associated with ceramics, glass, floor mosaic and minor metal objects – mostly military equipment and coins. Based on the analysis of architecture and finds it can be concluded that the camp was established in the early decades of the Principate. After legio VII left the fortress in the period of the mid-1 st century AD it had been used by smaller military units. They used – so for now it seems – only a part of the fortress. The military abandoned Tilurium not later than the mid-3 rd century.However, the fortress area then saw some minor activities like late antique burials.